Design of a current switching system for high accuracy current sources in AC-DC Transfer applications - Hernández Prada, CF; Sáchica Avellaneda, M; Martínez López, A; Sáchica Avellaneda, Mauricio; Martínez López, Alexander (IOP Publishing, 2021)
Abstract A current switching system for AC-DC transfer applications using Single Junction Thermal Converters (SJTC) was designed and tested at Instituto Nacional de Metrología (INM). This switch design can directly commute between a DC reference current source and an unknown AC current source generated by high accuracy calibrators such as Fluke 5720A and Fluke 5730A. Two vacuum latch relays with an estimated switching speed of less than 10 ms were used. A control unit developed over a MSP430 Microcontroller allowed the switching control and serial communication with instruments through LabVIEW. It was found that, it takes between 2 s and 3 s for high accuracy calibrators to switch between an operating DC current and an AC current, or vice versa; therefore, the current commutation time is limited by the calibrator. By using two calibrators and the implemented current switching system it was possible to reduce the commutation time to about 300 ms, which is less than the reported SJTC thermal time constant. The switching system must be fast enough to avoid the calibrators to go to a standby state. The research work showed that the switching system could be used to improve thermal converters operation for the calibration of high accuracy AC current sources and multimeters.